Sleep EEG maps the functional neuroanatomy of executive processes in adolescents born very preterm. (January 2017) - Wehrle, Flavia M.; Latal, Beatrice; O'Gorman, Ruth L.; Hagmann, Cornelia F.; Huber, Reto
Abstract: Executive function deficits are among the most frequent sequela of very preterm birth but the underlying neuronal mechanisms are not fully understood. We used high-density electroencephalography (EEG) recordings during sleep to assess alterations in the functional neuroanatomy of executive processes in adolescents born very preterm. The topographical distribution of sleep slow wave activity (SWA; 1–4.5 Hz EEG power) has previously been used to map cognitive abilities and is known to reflect the intensity of the prior use of the respective neuronal networks. We assessed 38 adolescents born before 32 weeks of gestation [age at assessment: 12.9 ( SD : 1.7), range : 10.6–16.7 years] and 43 term-born peers [13.1 (2.0), 10.0–16.9]. Executive function abilities were quantified with a composite score derived from a comprehensive task battery. All-night high-density EEG (128 electrodes) was recorded and SWA of the first hour of sleep was calculated. Abilities were significantly poorer in the very preterm compared to the term-group, particularly, if the tasks demands were high ( p < .01). The score was positively correlated with sleep SWA in a cluster of 15 electrodes over frontal and negatively in a cluster of 14 electrodes over central brain regions after controlling for age at assessment and correcting for multiple comparisons. Within the frontal cluster, sleep SWA was higher in very preterm compared to term-born participants when controlling for executive function performance and age at assessment ( p = .02). No difference in SWA between very preterm and term-born participants was found for the central cluster ( p = .29). Our results demonstrate a local increase of sleep SWA over brain regions associated with executive processes in adolescents born very preterm compared to similarly performing term-born peers. Thus, sleep SWA seems to map the higher effort needed for executive function tasks in adolescents born very preterm.